Computational simulations in coronary bifurcations: Paving the future of interventional planning. Issue 7 (16th June 2016) - Collet, Carlos; Serruys, Patrick W.
Key Points: Anatomical evaluation is of paramount importance in the treatment of bifurcation lesions. Left main coronary artery bifurcation geometry differs from left anterior descending artery/diagonal and circumflex artery/obtuse marginal bifurcations. Individualized approach with pre‐procedural planning has the potential to improve outcomes after bifurcation treatment.